2019
DOI: 10.1007/s13311-018-00707-y
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Periostin and Delayed Cerebral Ischemia After Aneurysmal Subarachnoid Hemorrhage

Abstract: Delayed cerebral ischemia (DCI) is a serious complication of aneurysmal subarachnoid hemorrhage (SAH). Matricellular protein periostin (POSTN) has been found to be upregulated and linked with early brain injury after experimental SAH. The aim of the present study was to investigate the relationship between plasma POSTN levels and various clinical factors including serum levels of C-reactive protein (CRP), an inflammatory marker, in 109 consecutive SAH patients whose POSTN levels were measured at days 1-12 afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 38 publications
0
17
1
Order By: Relevance
“…In clinical settings, Luo et al measured the serum periostin levels at admission and reported that higher levels of serum periostin were associated with a poorer clinical grade at admission, higher frequency of development of DCI, and worse neurological outcomes in the aSAH patients [66]. In a recent study conducted by our research group, plasma periostin levels were chronologically measured 4 times during the period between the post-operative or postinterventional Day 1 and post-aSAH Day 12; the plasma periostin levels were observed to peak at Day 4-6 after onset, and later, development of DCI was observed [39]. Although periostin is a kind of inflammatory marker [28], the study revealed that the plasma periostin levels exhibited no correlation with the serum levels of a systemic inflammatory marker named C-reactive protein [39].…”
Section: Periostin In Sah In Experimental and Clinical Settingsmentioning
confidence: 90%
See 4 more Smart Citations
“…In clinical settings, Luo et al measured the serum periostin levels at admission and reported that higher levels of serum periostin were associated with a poorer clinical grade at admission, higher frequency of development of DCI, and worse neurological outcomes in the aSAH patients [66]. In a recent study conducted by our research group, plasma periostin levels were chronologically measured 4 times during the period between the post-operative or postinterventional Day 1 and post-aSAH Day 12; the plasma periostin levels were observed to peak at Day 4-6 after onset, and later, development of DCI was observed [39]. Although periostin is a kind of inflammatory marker [28], the study revealed that the plasma periostin levels exhibited no correlation with the serum levels of a systemic inflammatory marker named C-reactive protein [39].…”
Section: Periostin In Sah In Experimental and Clinical Settingsmentioning
confidence: 90%
“…Although periostin is a kind of inflammatory marker [28], the study revealed that the plasma periostin levels exhibited no correlation with the serum levels of a systemic inflammatory marker named C-reactive protein [39]. However, cerebrospinal fluid drainage was observed to significantly lower the plasma periostin levels at all time points of measurement, possibly because the drainage of cerebrospinal fluid removed periostin before the latter moved from the brain extracellular fluid or the cerebrospinal fluid to peripheral blood [39]. Multivariate logistic regression analyses conducted using all the clinical variables by Day 3 post-aSAH demonstrated that the plasma periostin levels at Days 1-3 post-aSAH (post-operative or post-interventional Day 1) served as an independent predictor of DCI, irrespective of the subsequent development of cerebral vasospasm [39].…”
Section: Periostin In Sah In Experimental and Clinical Settingsmentioning
confidence: 92%
See 3 more Smart Citations